Analisis Penerapan Fiqih Muamalah Dalam Pengupahan Pengiriman Paket Barang Studi Kasus Pada PT. Lion Parcel Pos Cabang Medan - Azzahrawani, Deswana (Yayasan Rahmat Islamiyah, 2023)
This study aims to find out how the application of Fiqh Muamalah on the wage system or rounding off the scales at PT. Lion Parcel Pos Medan Branch. This study uses a qualitative research method that is descriptive in nature. The method used for data collection is the method of observation, interviews and documentation, which was carried out at Lion Parcel Pos Medan Branch. Research results at PT. Lion Parcel Pos Medan Branch found that there are two systems in rounding off the scales, namely the actual system and the volumetric system. From the results of interviews with Lion Parcel Pos Medan branch customers, there are customers who feel disadvantaged and there are those who feel they are not disadvantaged in the system of rounding off the scales that have been implemented. From the analysis that has been carried out by the author, if viewed based on an ijarah contract, the transaction has fulfilled the pillars and conditions. But when viewed from the Fiqh Muamalah rounding off of the scales, the results of weighing packages of goods at the Lion Parcel Pos Medan Branch expedition contain elements of gharar.